Discourse and identity - Benwell, Bethan; Stokoe, Elizabeth (Edinburgh University Press, 2006)
Identity' is a central organizing feature of our social world. Across the social sciences and humanities, it is increasingly treated as something that is actively and publicly accomplished in discourse. This book defines identity in its broadest sense, in terms of how people display who they are to each other. Each chapter examines a different discursive environment in which people do 'identity work': everyday conversation, institutional settings, narrative and stories, commodified contexts, spatial locations, and virtual environments. The authors describe and demonstrate a range of discourse and interaction analytic methods as they are put to use in the study of identity, including 'performative' analyses, conversation analysis, membership categorization analysis, critical discourse analysis, narrative analysis, positioning theory, discursive psychology and politeness theory. The book aims to give readers a clear sense of the coherence (or otherwise) of these different approaches, the practical steps taken in analysis, and their situation within broader critical debates. Through the use of detailed and original 'identity' case studies in a variety of spoken and written texts in order, the book offers a practical and accessible insight into what the discursive accomplishment of identity actually looks like, and how to go about analyzing it. Key Features . Accessible introduction to the study of discourse and identity across a variety of contexts. Interdisciplinary in scope, the book is relevant to a wide range of courses such as English language and linguistics, psychology, media, cultural studies, gender studies and sociology. Each chapter includes a critical overview of work in the area, original case studies, practical instruction for analyses, points for further discussion and suggested reading.